Web content and design trends of Alabama academic libraries. Issue 1 (2nd February 2015) - Wilson, Daniel Earl
Abstract : Purpose: – This paper aims to evaluate the website content of Alabama academic libraries to examine their services, content and compliance with design and accessibility standards. Design/methodology/approach: – A content analysis was conducted on 24 academic library websites discovered through Jeanne Burke's Higher Education Directory and the Alabama Colleges directory website. All data were collected within a month. Findings: – Study data revealed that while academic libraries are offering more online services, many continue to lack certain services or fail to implement basic web design and accessibility standards. Research limitations/implications: – Inclusion into the study was limited to the independent library websites of Alabama institutions offering four-year degree courses and content data discoverable within three clicks of the home page. Future studies might identify why certain libraries lack reference chat services, social media accounts and/or certain accessibility accommodations. Additional research might evaluate multilingual websites and their methods for providing language options. Practical implications: – The results of this study should assist in the evaluation of library websites and increase awareness of design and accessibility standards, enabling designers and policy makers to improve upon future website designs. Originality/value: – This study presents a depth of evaluation and currency unseen in most web content analyses. The extent of this study should provide librarians, web designers, and library policy makers with a suitable comparison for website projects and evaluations.